The effect of explicit and implicit teaching vocabulary on Iranian EFL learners vocabulary - Seyyed Taghi Yaghoubi; Fatemeh Seyyedi (Studies in English Language and Education, 2017)
This research aimed to find out and compare the effects of two types of teaching- learning vocabularies: explicit vs. implicit teaching-learning on building the EFL vocabulary of Iranian EFL students. The participants of the study were 100 intermediate females EFL students from four English classes. The instruments of this study included a PET test, a pre-test and a post-test. The researchers divided the sample into two groups which were given 15 sessions of treatment; the vocabulary items were taught explicitly to the Explicit Group (EG) by giving them the definitions of the words. However, to the second group, the Implicit Group (IG) the vocabulary items were taught implicitly by giving them example sentences in which the new words were used. After the treatments, a post-test was taken by the participants to examine the effects. The results showed that although both methods of teaching vocabulary were found to be effective, there was a significant difference between the post-test scores of the two groups; the EG which received explicit teaching-learning learnt much more vocabulary than the IG that received implicit teaching-learning of vocabulary. The findings of this study have several pedagogical implications in that they can make EFL teachers in Iran clearer about the more effective way for EFL classes to teach and learn vocabulary.